PENANAMAN KARAKTER SEHAT MELALUI EVENT TINJU TINGKAT PELAJAR - Siagian, Julya Sisilia; Nofrizal, Dedi; Andriansyah, Juan; Purba, Jhonindo; Sitorus, Josep Martumbur (Asosiasi Dosen Akutansi Indonesia, KEPRI, 2024)
Kegiatan